A lysosome-targeting viscosity-sensitive fluorescent probe based on a novel functionalised near-infrared xanthene-indolium dye and its application in living cells - Liu, Chang; Zhao, Tong; He, Song; Zhao, Liancheng; Zeng, Xianshun (Journal of materials chemistry. B, Materials for biology and medicine, 2020)
The viscosity of lysosomes plays a significant role in modulating biological processes and reflects the status and function of this kind of organelle, e.g. , locations, morphologies, and components. Herein, we constructed a novel near-infrared (NIR) lysosome-targeting viscosity probe, Lyso-cy , for monitoring viscosity changes in biological systems. The Lyso-cy probe showed very strong fluorescence emission at around 710 nm in viscous media. The fluorescence intensity of Lyso-cy increased 122-fold from when in water to when in 95% glycerol. Moreover, Lyso-cy proved to be an ideal lysosome-targeting tracer for monitoring fluctuations in the viscosity of a living cell with high spatial and temporal resolution under laser confocal microscopy. The viscosity of lysosomes plays a significant role in modulating biological processes and reflects the status and function of this kind of organelle, e.g. , locations, morphologies, and components.